Impact of environmental factors on photovoltaic performance and their mitigation strategies–A holistic review. (March 2019) - Ghosh, Santosh; Yadav, Vinod Kumar; Mukherjee, Vivekananda
Highlights: Presents holistic review of impact of environmental factors on PV performance. Covers impact of humidity, temperature, wind, aerosols and partial shading as well. Background, current research and mitigation approaches of each factors discussed. Balance has been maintained between the past research and very recent ones. Relevent review papers have been cited, wherever new discussions are redundant. Abstract : In the pursuit of a trade-off between the ever-increasing energy demand and greenhouse gas emissions, the world has reached an unprecedented stage, where the photovoltaic (PV) energy has become techno-commercially more attractive than any other means of energy conversion ever known to the mankind through continual innovations in manufacturing processes, project financing and execution. However, the commercial success of a PV project depends on its performance ratio over its useful lifetime, and unfortunately the performance ratio of PV project is highly sensitive to environmental factors unlike conventional and other renewable energy technologies. Performance ratio of PV systems not only depends on the intensity of irradiance but also on several other environmental factors viz . wave length of the incident irradiance; relative humidity, temperature and pollution level of the atmosphere; wind speed and its direction; rain fall pattern and its intensity, physical properties of the dusts and cloud movement pattern over the project site. Though numerous works have been reported on impact of some of the dominant environmental factors in the past, a comprehensive review is missing in the literature. This work presents a holistic review of impact of all the environmental factors on PV performance and their mitigation approaches.